Research on the efficiency evaluation of the integration of technology and finance in China’s strategic emerging industries - Yang, Qing; Zhao, Kunqiang; Cao, Lanjuan; Wang, Xiaohua; Guo, Qizhe; Liu, Xingxing (Frontiers in Psychology, 2023)
The combination of technology and finance has a great potential impact on regional social and economic development, and strategic emerging industries are the convergence of technological innovation and financial support, the development of which have great significance for industrial structure adjustment and industrial quality improvement. Aiming at strategic emerging industries in 18 provinces in China, we collect the data of 206 enterprises on the Science and Technology Innovation Board, use the Three-stage DEA model to measure the input-output efficiency of the integrated development of technology and finance and utilize the regression model to explore the path of the integrated development of technology innovation and financial support. The research finds that the development of strategic emerging industries has a large demand for financial support and obvious regional differences, and the government plays a strong guiding role in their development as well. At the end of the research, countermeasures and suggestions for the development of strategic emerging industries are given.